Climate Change Policy Responses for Canada’s Inuit Populations: The Importance of and Opportunities for Adaptation - Ford, J D; Pearce, T; Duerden, F; Furgal, C; Smit, B (2012)
We identify and examine how policy intervention can help Canada’s Inuit population adapt to climate change. In doing so we build upon completed community-based vulnerability assessments and take the next step, using understanding of how Inuit are experiencing and responding to climate change to identify and examine policy entry points. Specifically, we analyze how multiple levels of government in Canada can establish and strengthen conditions favorable for effective adaptation to help reduce the negative impacts of climate change on resource harvesting, travel, food systems, and community infrastructure. Our recommendations are of direct relevance to article 4 of the United Nations Framework Convention on Climate Change (FCCC), which stresses the importance of identifying measures to facilitate adequate adaptation, and are intended to support climate change policy development in Canada’s northern regions. Despite a focus on Inuit in Canada, recommendations for policy entry points have relevance for Indigenous peoples and northern communities in general, particularly those whose culture and livelihoods are closely linked to land-based aspects of traditional lifestyles.